IMPLEMENTASI UNDANG-UNDANG NO 33 TAHUN 2014 DAN TINJAUN MAQHASID ASY SYARIAH TERHADAP INDUSTRI GERAI ES CREAM MIXUE - Rahmat Husein Lubis; Ulfi Zulfikar Faridhun; Erika Ramadani (Yurisprudentia: Jurnal Hukum Ekonomi, 2023)
In the current era of 4.0, the food and beverage industry in Indonesia has changed according to the needs of the communitys. Realizing the needs of the Indonesian people who have a tropical climate, China will establish its industrial business in Indonesia and make products in the form of modern ice cream. The ice cream industry in China is called Mixue. The large number of foreign products entering Indonesia has made the Indonesian government especially concerned about maintaining halal food and minimums so it issued Law No. 33 of 2014 concerning Guarantees for Halal Products. The Indonesian government gave the task to the Ministry of Religion, then the Ministry of Religion established the Halal Product Assurance Organizing Body (BPJPH). This research method is an empirical juridical research, in which the researcher wants to examine more deeply the duties of the Halal Product Assurance Organizing Agency (BPJPH) in supervising and providing halal labeling to the Ice Cream Mixue Industry whether it is by Law No. 33 of 2014 concerning Assurance Halal products in maintaining the benefit of the ummah. The provisional results show that the Ice Cream Mixue Industry does not yet have a halal logo label from (BPJPH).